Divergent effects of straw and biochar single additions on soil water-heat-salt transport and corn productivity in arid salinized irrigation area - Yang, Wei; Zhang, Xiaomin; Zhao, Yibo; Zhang, Dongliang; Li, Junjie; Song, Riquan; Wang, Liping; Qu, Zhongyi (Frontiers in Plant Science, 2025)
Straw return and straw-derived biochar are promising practices for improving soil physicochemical properties and crop production. However, the integrated effects of a single application on soil moisture, heat, salinity transport, and their regulation mechanism on crop water use efficiency (WUE) in salt-affected soils are still understood deeply. Four amendments were used: control without any additives (CK), direct return of 10 t ha-1 straw (BJ), and biochar treatments of 15 t ha-1 (B15), and 30 t ha-1 (B30). Application of straw and biochar generally increased the soil moisture content during whole crop growth periods. Temperature in the top 10 cm of soil increased by 0.97°Cfor B30 and 1.08°C for BJ when averaged two growing seasons. The BJ led to a slight reduction in soil pH from 0~30 cm, while biochar application did not significantly increased soil pH during crop growth periods. B30 also did not increased soil salinity of top 30-cm depth while BJ increased soil salinity. The desalting ratio at 0~30 cm at maturity in BJ and B30 two amendments decreased slightly during the first growing season but increased during the second growing season across two years. Straw and biochar also enhanced crop yield, WUE, net income. These effects improved more in the first year than in the second year. The two-year average WUE and net profit values increased more for B30 than for BJ. Thus, B30 amendment is recommended to improve soil water-heat environment, crop WUE, and net income without significantly adjusting the degree of soil salinization.